Digital Pathology Displays Under Pressure: Benchmarking Performance Across Market Grades. - Marletta, Stefano; Caputo, Alessandro; Guidi, Gabriele; Pantanowitz, Liron; Pagni, Fabio; Bavieri, Iacopo; L'Imperio, Vincenzo; Brunelli, Matteo; Dei Tos, Angelo Paolo; Eccher, Albino (Journal of Imaging Informatics in Medicine, 2025)
Digital pathology (DP) has transformed the practice of pathology by digitizing pathology glass slides, thereby enhancing diagnostic capabilities. In contrast to radiology, studies comparing the efficiency of DP monitors are limited. This work used a stress test that simulated DP sign-out in practice to evaluate the performance of medical-grade (MG) and consumer off-the-shelf (COTS) displays. Four displays, including three MG and one COTS, were assessed for luminance, contrast ratio, accuracy, and image uniformity. Key metrics, such as luminance uniformity and maximum brightness, were evaluated during a 1-month period that simulated use to reflect an 8-h work day. MG displays outperformed COTS in critical parameters, even though consumer displays were satisfactory for diagnostic purposes. Image uniformity exhibited the most significant variations, with deterioration noted over 2.5% for all displays during the test period. This study compared different types of displays for DP and highlights the importance of regular calibration for maintaining display performance when using DP. Further research is recommended to define validation protocols, including the impact of display aging on DP accuracy.